HATE SPEECH AS A THREAT TO INCLUSIVE SOCIETIES: EXAMINING THE LIMITS OF FREE SPEECH - A. K. Barnwal; Sharma, Rohit (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The concern over hate speech is on the rise in contemporary countries, directly undermining initiatives to promote equality, inclusivity, and social cohesion. Despite being a fundamental component of democratic ideals, the abuse of free speech to incite hatred, violence, and discrimination presents serious moral and legal issues. This article examines the nuances of hate speech, emphasising the conflict between defending free speech and preventing harm to people and communities. It looks at the intellectual and legal underpinnings of free speech, emphasising how hate speech is defined and controlled by Indian, international, and covenantal legal systems. The article evaluates the practical effects of unrestrained hate speech, particularly its effects on inclusive societies and marginalised groups, using case studies and comparative analysis. The conversation concludes by taking into account international efforts and governmental solutions meant to achieve a balance between protecting free speech and prohibiting speech that compromises inclusivity.